Pemetaan Kesesuaian dan Variabilitas Iklim untuk Tanaman Jagung Berbasis Sistem Informasi Geografis (SIG) di Provinsi Bali - SATRIYABAWA, I KADEK MAS; LANYA, INDAYATI; SARDIANA, I KETUT (Agrotrop : Journal on Agriculture Science, 2023)
Mapping of Climate Suitability and Variability for Corn Based on Geographic Information System (GIS) . Each plant requires different growing conditions according to a certain climate. Climatic conditions can vary, such as El Nino and La Nina, which causes changes in the climate suitability of corn. Evaluation of climate suitability is important because climate factors are dynamic and difficult to control. This study aims to map the climate suitability of corn and map the climate suitability of corn when climate variability occurs in Bali Province. The analytical method used is matching and mapping using GIS. The results of this research showed that the climate suitability of normal period for corn in Bali Province is quite suitable (S2) and mostly (89.33%) is marginal (S3). Based on the limiting factors, it is divided into S2tc, S2wa, S2watc, S3wa and S3watc with the majority (498,568.26 ha) being S3wa. In general, climate variability causes changes in the area suitable for planting corn in Bali Province. El Nino had an impact on increasing the S2 area in the 2015 strong El Nino so that the S2watc area became 214,324.27 ha and the overall S2 area became 44.53%. The strong La Nina in 2010 reduced the overall S2 area to 0.49%, especially S2watc remaining only 2,756.75 ha.